Second Harmonic Generation Microscopy in Zebrafish - LeBert, Danny C. (Methods Cell Biol, 2016)
Modern optical imaging has progressed rapidly with the ability to non-invasively image cellular and subcellular phenomena with high spatial and temporal resolution. In particular, emerging techniques such as Second Harmonic Generation Microscopy (SHG) can allow for the monitoring of intrinsic contrast, such as that from collagen, in live and fixed samples. When coupled with multiphoton fluorescence microscopy, SHG can be used to image interactions between cells and the surrounding extracellular environment. There is recent interest in using these approaches to study inflammation and wound healing in zebrafish, an important model for studying these processes. In this chapter we present the practical aspects of using second harmonic generation to image interactions between leukocytes and collagen during wound healing in zebrafish.